2017
DOI: 10.2139/ssrn.3083886
|View full text |Cite
|
Sign up to set email alerts
|

Is the Thai Government Revenue-Spending Nexus Asymmetric?

Abstract: This paper examines the relationship between government revenue and spending in Thailand using a nonlinear framework. Both TAR and MTAR models are estimated. The empirical results from the estimate of the TAR model show the presence of asymmetry in the long-run relationship between revenue and spending. The results of short-run dynamics indicate that both revenue and spending respond to budgetary disequilibrium when there is improving government budget. Furthermore, bidirectional causality is found. The eviden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Similarly, Jiranyakul [19] has found that the spend-tax hypothesis is valid in the case of Thailand. Narayan [20] estimated the fiscal causality in Southeast Asian countries, i.e., Indonesia and Singapore, using the ARDL technique.…”
Section: Literature Reviewmentioning
confidence: 91%
“…Similarly, Jiranyakul [19] has found that the spend-tax hypothesis is valid in the case of Thailand. Narayan [20] estimated the fiscal causality in Southeast Asian countries, i.e., Indonesia and Singapore, using the ARDL technique.…”
Section: Literature Reviewmentioning
confidence: 91%
“…Furthermore, Omoshoro-Jones (2020) examines government revenue-expenditure nexus for the Free State Province and the study found a bidirectional causality subsists between government revenues and expenditures in the Province. Moreover, Jiranyakul (2017) confirms a bidirectional causality between government revenue and expenditure in Thailand. Similarly, Hye and Jalil (2010)'study indicates a bidirectional causality between Romanian government expenditure and revenue.…”
Section: Literature Reviewmentioning
confidence: 55%
“…This suggests that that the two variables of study are cointegrated which implies that there is a long-run relationship between government revenue and expenditure of the States government and Federal Capital Territory of Nigeria. Jiranyakul (2017) in Thailand; Hye and Jalil (2010) in Romania; Soomro (2020) in Pakistan; Phiri (2016); Takumah (2014) in Ghana. In the Nigerian context, some studies have also confirmed the validity of the fiscal synchronization hypothesis at the federal government level (Saka et al (2015), Aminu and Raifu (2018), Ibrahim (2018), Eniekezimene, et al (2019), Aladejare and Ani (2012)).…”
Section: Cointegration Testsmentioning
confidence: 99%
See 1 more Smart Citation